The Influence of Work Discipline, Compensation, and Leadership on Turnover Intention: Evidence from Employees of PT. Sumber Alam Makmur - Irwan Supriyanto; Makmur Makmur; Endah Arianti Putri (International Journal of Economic and Tourism Research, 2026)
This study examines the effects of work discipline, compensation, and leadership on turnover intention among employees of PT. Sumber Alam Makmur Sentosa (PT SAMS), a palm oil plantation company in Rokan Hulu, Riau. The study was motivated by increasing employee mobility and indications of sustained turnover pressure within the company over the past five years. A quantitative approach was employed using a structured questionnaire distributed to 87 employees selected through simple random sampling from a total population of 111 workers. Data were analyzed using multiple linear regression after passing validity, reliability, and classical assumption tests.The results indicate that partially only leadership significantly influences turnover intention, while work discipline and compensation do not show significant effects. Simultaneously, the three independent variables do not significantly explain turnover intention. The coefficient of determination (R² = 0.058) demonstrates that the model has low explanatory power, suggesting that turnover intention is influenced by other psychological and contextual factors beyond discipline and compensation.These findings imply that improving leadership quality, particularly in terms of communication, responsiveness, and perceived fairness, is more critical for employee retention than relying solely on disciplinary enforcement or compensation adjustments. The study contributes to human resource management literature by highlighting the contextual nature of turnover intention in plantation-based organizations.